Chemo-mechanical analysis of ratcheting deformation in silicon particle electrode under cyclic charging and discharging. (November 2021) - Shi, Yutao; Weng, Li; Zhang, Yudong; Xu, Chengjun; Chen, Qilu; Chen, Bingbing; Zhou, Jianqiu; Cai, Rui
Abstract: Evidences have accumulated that high capacity silicon electrode will expand/shrink dramatically during cyclic charging/discharging operation. In this process, the electrode may undergo elastic-inelastic deformation, and cyclic asymmetric behavior of tension and compression can naturally result in the electrode ratcheting deformation. In this paper, a chemo-mechanical semi-analytical model is established to describe the ratcheting behavior of the silicon particle electrode based on concentration-dependent material properties. The results show that inelastic deformation can reduce the rapid increase of the stresses and further reduce the possibility of surface crack. However, the accumulated irreversible inelastic strain may become one of the important factors for mechanical degradation and even electrode failure. The influence of hydrostatic stress on electrode ratcheting behavior is discussed in detail. It can decrease the concentration gradient and stress level, thereby reducing the inelastic region and ratcheting deformation, which will prolong the predicted lifetime of the electrode. The diffusion coefficient, particle size and the charging rate have also been investigated. The results reveal that ratcheting deformation may be decreased by the high diffusivity, the small particle size and slow charging strategy, which will improve the mechanical stability and capacity of the electrode. Meanwhile, interparticle contact may worsen the ratcheting deformation. Increasing the electrode porosity appropriately can provide space for silicon particles to expand, which may reduce the ratcheting deformation. The present work gives a new explanation for ratcheting deformation in silicon particle electrode and provides a theoretical basis for guiding one in designing next-generation high capacity lithium-ion batteries. Graphical abstract: Image 1 Highlights: The chemo-mechanical model of silicon electrode ratcheting deformation is raised. Electrode ratcheting deformation may cause mechanical degradation and failure. Hydrostatic stress has an impact on ratcheting deformation and electrode lifetime. Ratcheting deformation decreases with reduction of electrode size and charging rate. Interparticle contact affected by porosity may worsen the ratcheting deformation.